2012
DOI: 10.4103/1817-1745.97611
|View full text |Cite
|
Sign up to set email alerts
|

Role of electroencephalogram and neuroimaging in first onset afebrile and complex febrile seizures in children from Kashmir

Abstract: Objectives:(1) To determine the frequency of abnormal neuroimaging in children with new-onset afebrile and complex febrile seizures; (2) to draw a correlation between Electroencephalogram (EEG) and neuroimaging.Study Design:A hospital-based prospective study.Materials and Methods:A total of 276 children (6 months to 14 years of age), who presented with new-onset afebrile or complex febrile seizures, underwent EEG and neuroimaging [Computed Tomography (CT) and/or Magnetic Resonance Imaging (MRI)].Results:Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our study reflected abnormal EEG in the complex febrile seizures in 2% cases, similar to another study on febrile seizures in children [25][26][27]. Another study reported that 20% of undetermined seizure cases had an abnormal EEG [28]. In our study, 5% of undiagnosed cases and 159 cases of generalized seizure had an abnormal EEG.…”
Section: Discussionsupporting
confidence: 90%
“…Our study reflected abnormal EEG in the complex febrile seizures in 2% cases, similar to another study on febrile seizures in children [25][26][27]. Another study reported that 20% of undetermined seizure cases had an abnormal EEG [28]. In our study, 5% of undiagnosed cases and 159 cases of generalized seizure had an abnormal EEG.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Rasool A et al, found out that abnormal EEG increases the risk of having abnormal neuroimaging but also reported that normal EEG does not rule out having an abnormal neuroimaging. Therefore they concluded that clinical examination and EEG results are good indicators and can be used as one of the criteria for ordering neuroimaging in new-onset seizures, more so in partial than generalized seizure [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every Child presenting with partial seizures must undergo EEG and imaging study like CT scan, as both collectively help in establishing the etiology of partial seizure and thus serves as a reliable guide for appropriate management. 11,12…”
Section: Discussionmentioning
confidence: 99%